1989
DOI: 10.1159/000238673
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of High-Dose versus Low-Dose cis-Platinum Combined with Cyclophosphamide in the Treatment of Advanced Ovarian Cancer

Abstract: A randomized clinical study of patients with advanced epithelial ovarian cancer after debulking surgery showed that high-dose (120 mg/m2) cis-platinum (DDP) in combination with cyclophosphamide (600 mg/m2) had a significantly higher response and survival rate than the low-dose DDP (60 mg/m2) and cyclophosphamide combination. The 3-year actuarial survival rate of the high-dose group was 60% and that of the low-dose group was 30%. Though moderate to severe marrow toxicity was evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(21 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…The earliest of these studies (Ngan et al , 1989) was carried out in 50 assessable patients with debulked advanced epithelial ovarian cancer, and showed 3-year actuarial survival rates of 60 and 30% for high-dose (120 mg m −2 ) and low-dose (60 mg m −2 ) cisplatin, respectively (both given every 3–4 weeks in combination with cyclophosphamide 600 mg m −2 ). Notwithstanding this impressive difference between groups, some doubt has been attached to the results of this study because of the small size of the patient cohort studied and because baseline disease characteristics were not fully characterised.…”
Section: Strategies For Modulating Drug Resistancementioning
confidence: 99%
“…The earliest of these studies (Ngan et al , 1989) was carried out in 50 assessable patients with debulked advanced epithelial ovarian cancer, and showed 3-year actuarial survival rates of 60 and 30% for high-dose (120 mg m −2 ) and low-dose (60 mg m −2 ) cisplatin, respectively (both given every 3–4 weeks in combination with cyclophosphamide 600 mg m −2 ). Notwithstanding this impressive difference between groups, some doubt has been attached to the results of this study because of the small size of the patient cohort studied and because baseline disease characteristics were not fully characterised.…”
Section: Strategies For Modulating Drug Resistancementioning
confidence: 99%
“…Two studies compared higher (100Y120 mg/m 2 ) and lower doses (50Y60 mg/m 2 ) of cisplatin in combination with cyclophosphamide (600Y750 mg/m 2 ). 8,9 Although both RCTs reported that a higher dose of cisplatin improved survival and response rate, they also reported significant increases in myelosuppression, neurotoxicity, and ototoxicity. Sizes of both trials were small (50 and 165 patients), and one of them ended early.…”
Section: Resultsmentioning
confidence: 99%
“…Only three small randomized trials have, so far, showed a significant survival benefit for higher doses of CDDP (27,31,32) . The largest of these trials was prematurely closed after the interim analysis, at 2 years of follow-up, showed an increased median survival with high-dose CDDP (114 versus 69 weeks; P ¼ 0.0008; HR ¼ 0.68).…”
Section: Optimal Doses and Dose Intensity Platinum Agentsmentioning
confidence: 99%